Patents versus subsidies: A laboratory experiment - Donja Darai; Jens Großer; Nadja Trhal (University of Zurich, Socioeconomic Institute, 2009)
This paper studies the effects of patents and subsidies on R&D investment decisions. The theoretical framework is a two-stage game consisting of an investment and a market stage. In equilibrium, both patents and subsidies induce the same amount of R&D investment, which is higher than the investment without governmental incentives. In the first stage, the firms can invest in a stochastic R&D project which might lead to a reduction of the marginal production costs and in the second stage, the firms face price competition. Both stages of the game are implemented in a laboratory experiment and the obtained results support the theoretical predictions. Patents and subsidies increase investment in R&D and the observed amounts of investment in the patent and subsidy treatment do not differ significantly across both instruments. However, we observe overinvestment in all three treatments. Observed prices in the market stage converge to equilibrium price levels.
Keywords: C90; L13; O31; 330; R&D investment; oligopoly; patents; subsidies; experiment; Investition; Patent; Subvention; Oligopol; Test